Basic Theory and Laboratory Experiments in Measurement and Instrumentation : A Practice-Oriented Guide /: A Practice-Oriented Guide. (2020) - Cataldo, Andrea; Giaquinto, Nicola; De Benedetto, Egidio; Masciullo, Antonio; Cannazza, Giuseppe; Lorenzo, Ilaria; Nicolazzo, Jacopo; Meo, Maria Teresa; De Monte, Alessando; Parisi, Gianluca; Gaetani, Federico
No abstract available